Phosphate-assisted phytoremediation of arsenic by Brassica napus and Brassica juncea: Morphological and physiological response. Issue 7 (3rd July 2017) - Niazi, Nabeel Khan; Bibi, Irshad; Fatimah, Ayesha; Shahid, Muhammad; Javed, Muhammad Tariq; Wang, Hailong; Ok, Yong Sik; Bashir, Safdar; Murtaza, Behzad; Saqib, Zulfiqar Ahmad; Shakoor, Muhammad Bilal
ABSTRACT: In this study, we examined the potential role of phosphate (P; 0, 50, 100 mg kg −1 ) on growth, gas exchange attributes, and photosynthetic pigments of Brassica napus and Brassica juncea under arsenic (As) stress (0, 25, 50, 75 mg kg −1 ) in a pot experiment. Results revealed that phosphate supplementation (P100) to As-stressed plants significantly increased shoot As concentration, dry biomass yield, and As uptake, in addition to the improved morphological and gas exchange attributes and photosynthetic pigments over P0. However, phosphate-assisted increase in As uptake was substantially (up to two times) greater for B. napus, notably due to higher shoot As concentration and dry biomass yield, compared to B. juncea at the P100 level. While phosphate addition in soil (P100) led to enhanced shoot As concentration in B. juncea, it reduced shoot dry biomass, primarily after 50 and 75 mg kg −1 As treatments. The translocation factor and bioconcentration factor values of B. napus were higher than B. juncea for all As levels in the presence of phosphate. This study demonstrates that phosphate supplementation has a potential to improve As phytoextraction efficiency, predominantly for B. napus, by minimizing As-induced damage to plant growth, as well as by improving the physiological and photosynthetic attributes.